Imaging therapy response of gastrointestinal stromal tumors (GIST) with FDG PET, CT and MRI: a systematic review - Dimitrakopoulou-Strauss, Antonia; Ronellenfitsch, Ulrich; Hohenberger, Peter; Henzler, Thomas; Sachpekidis, Christos (Clinical and translational imaging, 2017)
Purpose Improvement of the therapeutic approaches in gastrointestinal stromal tumors (GIST) by the introduction of targeted therapies requires appropriate diagnostic tools, which allow sufﬁcient assessment of therapeutic response, including differentiation of true progression from pseudoprogression due to myxoid degeneration or intratumoral hemorrhage. In this literature review the impact and limitations of different imaging modalities used in GIST therapy monitoring are discussed.
Gesehen am 28.11.2018